THE ROLE OF REVELATION AND REASON IN CONSTRUCTING ISLAMIC ECONOMIC RATIONALITY AMID OF THE MODERN ECONOMY - Hendarti, Ricca; Yafiz, Muhammad (Journal of Sharia Economics, 2026)
Economic rationality in modern economics is generally constructed upon instrumental rationality that emphasizes efficiency and the maximization of individual self-interest in economic decision-making. While this approach has proven effective in promoting economic growth, it tends to marginalize normative values, ethical considerations, and social responsibility. In this context, Islamic economics offers an alternative perspective through the integration of revelation (wahy) and reason (‘aql) as the foundation of economic rationality. This article aims to examine and construct the concept of Islamic economic rationality based on the integration of revelation and reason within the framework of modern economic challenges. This study employs a qualitative approach with a conceptual–philosophical research design based on a literature review of relevant books and scholarly journal articles. The findings indicate that Islamic economic rationality does not position reason as an autonomous authority, but rather situates it within the normative framework established by revelation. Revelation provides moral direction and normative boundaries for economic activity, while reason functions to operationalize these values rationally and contextually. The integration of revelation and reason produces a form of economic rationality that is not only technically efficient but also morally oriented and committed to justice and social well-being. This study affirms that Islamic economic rationality represents an effort to reconstruct economic rationality so that it remains aligned with ethical values and humanistic objectives, making it conceptually relevant in responding to the complexities of modern economic systems.